Correlation of serology with morphological changes in gastric biopsy of H. pylori infection - Rajan, Amit; Ganguli, Prosenjit; Pathak, Niloy; Ranjan, Amar; Thapa, Ragini; Tripathi, Snehlata (International Journal of Research in Medical Sciences, 2017)
Background: Helicobacter pylori is involved in many gastrodeudonal complications and many diagnostic tests are available for its identification. The present study was done with the objective to evaluate the morphological changes induced by H. pylori in the gastric mucosa and to correlate them with the severity of the infection. Methods: This study was conducted in a tertiary care hospital from July 2013 to June 2014. 60 patients with symptoms of dyspepsia and requiring an upper gastrointestinal endoscopy were included in the study. Upper gastrointestinal endoscopy was performed on all patients. Hematoxylin and Eosin staining (H and E), modified Giemsa staining were performed on tissue sections and examined microscopically for gastritis and presence and absence of H. pylori. Results: Out of 60 patients, 33 were male and 27 were females. Serology by immunochromatography technique was positive in 41 patients. Serology was found to have a sensitivity and specificity of 90.90% and 59.25% respectively. H. pylori was positive in 28 cases on H and E. With a sensitivity and specificity of 84.84% and 100% respectively. H. pylori was positive in 33 cases on modified Giemsa with a sensitivity and specificity of 100%. Conclusions: Simultaneous morphologic and serological detection of H. pylori helps in its complete distribution and identification of its precancerous morphological nature.